Copper removal from aqueous solution using Amberlite IR-120 cation exchanger mixed matrix membrane chromatography - Zuraidah, Mohamad (2013)
Copper is one of the toxic heavy metals that contaminated in industrial wastewater. Cation exchange chromatography is widely used for the removal of copper (II)from the water. In this study, Amberlite IR-120 cation exchanger resin was used to prepare mixed matrix membrane (MMM) chromatography by blending the resin in ethylene vinyl alcohol (EVAL) base polymer solution. The EVAL composition was varied in the range of 15to 20 wt% with fixed Amberlite IR-120 loading at 30%. The adsorption isotherm of cation MMM was determined from batch binding experiment. From the result, it shows that MM15, prepared at 15 wt% EVAL gave high amount of copper binding of 5688.190 mg Cu/g adsorbent.In regeneration experiments using 0.1M HCl, more effective regeneration was showed byMMM20, prepared at 20 wt% EVAL, than EVAL membrane.